Age and Staphylococcus aureus Inoculation Route Differentially Alter Metabolic Potential and Immune Cell Populations in Laying Hens - Fries-Craft, Krysten; Meyer, Meaghan M.; Sato, Yuko; El-Gazzar, Mohamed; Bobeck, Elizabeth A. (Frontiers in Veterinary Science, 2021)
In 2018 and 2019, Staphylococcus aureus was isolated from multiple post-molt commercial laying hens with unusually high mortality. A challenge study was conducted to elucidate the role of S. aureus in this disease outbreak and the work herein represents the assessment of immunological responses in laying hens experimentally infected with S. aureus isolates from these cases. A total of 200 laying hens at 22 or 96 weeks of age (100/ age group) were assigned to 1 of 4 experimental inoculation groups (negative control, oral gavage, subcutaneous injection, or intravenous injection) after a 72h acclimation period. Blood samples were taken prior to inoculation (baseline), 6h post-inoculation (pi), 24hpi, 3dpi, and 7dpi. Additional spleen samples to further assess systemic immunity were taken at baseline, 3dpi, and 8dpi. Metabolic phenotypes of peripheral blood mononuclear cells (PBMC) were isolated and assessed by Seahorse metabolic assay. Immune cell profiles in the spleen and PBMC were assessed by multicolor flow cytometry. At baseline, 96-week-old laying hens had 26.7% fewer PBMC-derived T cells compared to 22-week-old birds. Older hens had 28.9% increased helper T cell (TH) populations and 60.5% reduced γδ T cells (P = 0.03 and < 0.0001) which may contribute to variable clinical responses between age groups; however, no age-related differences in metabolic potential were observed. Metabolic outcomes showed that birds remained stressed from transport and re-housing past a 72h acclimation period and through 24h- 3 days post-inoculation. Inoculation with S. aureus generally reduced oxidative and glycolytic potentials compared to the control, with the greatest reductions observed in birds inoculated by intravenous injection (P < 0.05). Overall CD3+ T cell populations showed significant reductions in the intravenous group compared to other inoculation routes from 24hpi to 7dpi (23.6-39.0%; P ≤ 0.0001). These results suggest that age-related baseline differences in T cell populations and changes to T cell subpopulations and other immune cells due to inoculation route may have an additive effect on S. aureus- induced reductions in metabolic potential; however, further research linking metabolic potential and immune cell profiles is needed.